Approaches to nitrogen fixation and recycling in closed life-support systems - Wallentine, Tyler; Merkley, David; Langenfeld, Noah J.; Bugbee, Bruce; Seefeldt, Lance C. (Frontiers in Astronomy and Space Sciences, 2023)
N2 fixation is essential to the sustainability and operation of nitrogen systems but is energetically expensive. We developed a model and used sensitivity analysis to identify the impact of aerobic and anaerobic waste digestion, crop harvest index, rates of recovery of recalcitrant N, and the rate of N2 fixation in a system combining nitrogen fixation and recycling. The model indicates that the rate of N2 fixation, loss from reactors, fertilization efficiency, and crop harvest index have the largest impact on maintaining bioavailable N. N recoveries from aerobic and anaerobic digestion, as well as direct-to-soil fertilization, are not well characterized, but the case studies using this model indicate that their efficiencies are critical to N recovery. The findings of this model and its presented case studies can be used as a guide in the design of closed-loop habitats both on Earth and in space. These results reveal a clear need for continued research in the areas of N-efficient digestion, fertilization, and fixation.